Challenges in Diagnosing and Initial Treatment of Advanced Eyelid Basal Cell Carcinoma in Rural Area: A Case Report: Poster Presentation - Case Report - General practitioner - Willy Yahya; Eunike Cahyaningsih (Majalah Oftalmologi Indonesia, 2023)
Introduction : Basal cell carcinoma (BCC) is the most common non-melanoma eyelid cancer with a high risk of recurrence. This case report discusses the management of extensive BCC in a rural setting with limited resources. Case Illustration : A 62-year-old Timorese female, presented to the hospital with a mass on the left periocular region. It appeared as a mole in the lower left eyelid and extended to the surrounding tissues over nine years. As a farmer, she was frequently sun-exposed. A blackish mass was found at the left orbit, buccal, and entire nose (8 x 7.5 cm) with an ulcerated surface and attached firmly. The right eye had bedside visual acuity >6/60, with palpebral edema, free eye movement, hyperemia nasal conjunctiva, and transparent cornea. The left eye is difficult to examine. Two submandibular lymphadenopathies were palpated. A Head CT scan showed a suspected malignant soft tissue mass with irregular thickening of soft tissue with ill-defined borders. Histopathology examination revealed a nodulocystic type of basal cell carcinoma. Discussion : Locally advanced BCC cases need a multidisciplinary approach. In a limited resources setting, the treatment highlights are histological diagnosis, complete surgical excision, and exenteration with margin control. From a broader perspective, the role of primary health care in educating and revering for early treatment is paramount. Conclusion : Prevention and early treatment are the most important factors in managing locally advanced BCC.